Measurement the Levels of Catalase Activity, Malondialdehyde and Ferritin in Beta-thalassemia Major Patient (Medico Legal Update, 2021)
The present study has been carried out at the Women’s and Educational Children’s Hospital in the city ofSamawa to determine the level of oxidative stress indicators and level ferritin. 66 samples of a patient withbeta-thalassemia major were collected and observation of some clinical signs was followed, the group of apatient was divided into two subgroups according to the splenectomy, Group One (G1)) Included 52 samplesfrom beta-thalassemia major patients, type non-splenectomy, (G2) included 14 samples from thalassemiapatients splenectomy and 34 samples were collected from healthy males as control samples (C) to measurethe level the activity of Catalase enzyme (CAT) and concentration levels of malondialdehyde MDA asoxidative stress indicators by using the Spectrophotometer and level ferritin using vidas. The results showeda significant decrease (p